The Oxford handbook of early Southeast Asia - Higham, Charles F.W; Kim, Nam C. (Oxford University Press, 2022)
Southeast Asia is one of the most significant regions in the world for tracing human prehistory over a period of 2 million years. Migrations from the African homeland saw settlement by Homo erectus and Homo floresiensis. Anatomically Modern Humans reached Southeast Asia at least 60,000 years ago to establish a hunter-gatherer tradition, adapting as climatic change saw sea levels fluctuate by over 100 metres. From about 2000 BC, settlement was affected by successive innovations that took place to the north and west. The first rice and millet farmers came by riverine and coastal routes to integrate with indigenous hunters. A millennium later, knowledge of bronze casting penetrated along similar pathways. Copper mines were identified, and metals were exchanged over hundreds of kilometres as elites commanded access to this new material. This Bronze Age ended with the rise of a maritime exchange network that circulated new ideas, religions and artefacts with adjacent areas of present-day India and China. Port cities were founded as knowledge of iron forging rapidly spread, as did exotic ornaments fashioned from glass, carnelian, gold and silver. In the Mekong Delta, these developments led to an early transition into the state known as Funan. However, the transition to early states in inland regions arose as a sharp decline in monsoon rains stimulated an agricultural revolution involving permanent ploughed rice fields. These twin developments illuminate how the great early kingdoms of Angkor, Champa and Central Thailand came to be, a vital stage in understanding the roots of modern states"-- |c Provided by publisher.